สาระสำคัญเกี่ยวกับโรคของเยื่อหุ้มหัวใจ - Ruangpratheep, Chetana (เวชสารแพทย์ทหารบก, 2019)
Abstract: Generally, diseases of the pericarcium is uncommon, i.e. pericardial effusion, cardiac tamponade, pericarditis, and peicardial neoplasms (tumours). However, cardiac tamponade is one of the important cause of sudden death. A good understanding of the aetiologies of pericardial abnormalities can lead to improve the patient’s care throughout diagnosis and treatment.